PENGARUH IMPLEMENTASI TAX AMNESTY TERHADAP PENINGKATAN PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA SAMARINDA ULU - Aisyah Nazwa Az Zahra; Imam Nazarudin Latif; Ivana Nina Esterlin Barus (ICMA Nasional, 2025)
This research sees tax amnesty as a government policy to increase the number of taxpayers and improve compliance. By removing previous tax debts and sanctions, this policy encourages non compliant taxpayers to return, and helps increase tax revenue and restoring public trust in the government. This study aims to determine and analyze what effect the implementation of Tax Amnesty Volume 2 has on increasing tax revenue at Kantor Pelayanan Pajak Pratama Samarinda Ulu. The theoretical basis used in this research is the concept of taxation, tax amnesty, and tax revenue. This research applies a quantitative approach with a minimum sample of 96 respondents, determined using the Lameshow formula, and a purposive sampling technique. Primary data were collected through direct observation and questionnaires completed by respondents. Data analysis was conducted using WarpPLS 7.0 with the Structural Equation Modelling (SEM) approach. The results show that the implementation of tax amnesty has a positive and significant influence on the increase in tax revenue at Kantor Pelayanan Pajak Pratama Samarinda Ulu. These findings indicate that the policy provides a tangible contribution to optimizing tax revenue, particularly through improved compliance among previously inactive taxpayers. This research is expected to serve as a reference for companies to enhance their compliance and transparency regarding post tax amnesty obligations as a basis for readers to develop broader studies on fiscal policy and as a consideration for future researchers to adopt a nonlinear approach in analyzing variable relationships to obtain more accurate and realistic results